Dynamic thermal model for proton-exchange membrane fuel cell - Mohamed Idres, Moumen; Kafafy, Raed (2010)
In this paper, a mathematical model is developed to simulate the transient phenomena in a polymer electrolyte membrane fuel cell (PEMFC) system. Large transient changes are expected for practical application such as transportation vehicles due to acceleration and deceleration. Simple models are usually unable to capture these transient dynamics. For control purposes, a fuel cell model must include the dynamics of flow and pressure in the anode and cathode channels and mass/heat transfer transients. The proposed model can predict the transient response of cell voltage, temperature of the cell, hydrogen/oxygen out flow rates and cathode and anode channel pressures under sudden change in load current. It is implemented in SIMULINK environment. The model is tested by simulating a transportation-size fuel cell with 85 kW maximum power output. Results for maximum power and multi-step input current that simulate start up-shut down cycle are shown. The predicted power, pressure and temperature are matching the published data for the fuel cell. The model will be very useful for the optimal design and real-time control of PEM fuel cell systems in practical automotive or stationary applications.